Valorization of Peanut Skin as Agricultural Waste Using Various Extraction Methods: A Review - Nicky Rahmana Putra; Dwila Nur Rizkiyah; Mohd Azizi Che Yunus; Ahmad Hazim Abdul Aziz; Ahmad Shah Hizam Md Yasir; Irianto Irianto; Jumakir Jumakir; Waluyo Waluyo; Suparwoto Suparwoto; Lailatul Qomariyah (Molecules, 2023)
Peanuts (Arachis hypogea) can be made into various products, from oil to butter to roasted snack peanuts and candies, all from the kernels. However, the skin is usually thrown away, used as cheap animal feed, or as one of the ingredients in plant fertilizer due to its little value on the market. For the past ten years, studies have been conducted to determine the full extent of the skin’s bioactive substance repertoire and its powerful antioxidant potential. Alternatively, researchers reported that peanut skin could be used and be profitable in a less-intensive extraction technique. Therefore, this review explores the conventional and green extraction of peanut oil, peanut production, peanut physicochemical characteristics, antioxidant activity, and the prospects of valorization of peanut skin. The significance of the valorization of peanut skin is that it contains high antioxidant capacity, catechin, epicatechin resveratrol, and procyanidins, which are also advantageous. It could be exploited in sustainable extraction, notably in the pharmaceutical industries.